Becoming the Unseen Helmsman - Game facilitator competencies for novice, experienced, and non-game facilitators. (June 2021) - Kortmann, Rens; Peters, Vincent
Background . To facilitate game sessions for purposes beyond mere entertainment a facilitator needs to act like an 'Unseen Helmsman': steering their ship clear from rocks and storms without the players in the ship realizing. Previous work laid down a competency model forgame facilitation . It reviewed several competency models for facilitators of generic (non-game) group sessions. Since no such model comprehensively provided guidelines to facilitate game sessions in particular, a new competency model was proposed using a bottom-up approach with the participation ofgame facilitation experts. The question remains what lessons may be drawn from this model. Methods. This contribution elaborates on thecompetency model for game facilitation and draws lessons from it. Thus it aims to empower both novice and experiencedgame facilitators to become an Unseen Helmsman. Also, it presents learnings for people who are experienced in facilitating groups in general, but who are new to facilitating game sessions. Conclusions. First, lessons for novice game facilitators include familiarising themselves with the core notions of thecompetency model : the characteristics of a complex systems game (session), and the attitudes, knowledge, and skills for successfulgame facilitation . Second, experienced game facilitators may learn from existingcompetency models for generic (non-game)group facilitation . Third, facilitators of generic (non-game) group sessions are encouraged to study the characteristics of game sessions in addition to the specific competencies contained in thecompetency model for game facilitators.